Inguinal Hernia with Splenic Incarceration in a Male Dog - Araújo Vasconcelos, Bárbara Michelle; de Freitas, Dilma Mendes; Moreira, Priscila de Paula; Teixeira Amado Jorge, Ana Luiza; Piva Maria, Bruna; Ângelo Benato, Tarcísio; Rodrigues Rosado, Isabel; Leonel Alves, Endrigo Gabellini (Acta Scientiae Veterinariae, 2020)
Background: Hernias are changes with the displacement of organs from their normal anatomical location to a newly formed cavity, which can cause pain and dysfunction of the affected organ. The diagnosis can be obtained by palpation or by ultrasound. The treatment of choice is surgical and vision to promote the return of the organ to its normal anatomical position and the closure of the hernial ring. When affixing the edges of the hernial ring is not possible, alternative techniques such as the use of biological or synthetic membranes should be sought. The aim of the present study is to report an atypical case of inguinal hernia with splenic incarceration, in which splenectomy and herniorrhaphy with a bovine phrenic center were performed. Case: An 8-year-old large mestizo male dog was referred to the Veterinary Hospital of Uberaba complaining of the appearance of a mass in the inguinal region that increased significantly in the last 15 days. On physical examination, there was an increase in volume in the left inguinal region, irreducible and great pain sensitivity in the region. The hemogram showed normochromic normocytic anemia, hyperproteinemia and thrombocytopenia. No changes were observed in the biochemical analyzes. Urinalysis revealed the presence of protein and traces of occult blood. Ultrasound showed an enlarged spleen inside the hernial sac, closing the diagnosis of inguinal hernia. The animal underwent a herniorrhaphy procedure associated with the use of a biological membrane from a bovine phrenic center and splenectomy. In addition, contralateral inguinal hernia was observed. The animal remained hospitalized and under observation for three days. On return, after five days, the guardian reported that the animal was urinating by dripping and had increased volume in the region of the surgery. Urethral catheterization was performed without difficulty and the region of swelling was punctured, obtaining a serosanguinous liquid. Ten days after surgery, stitches were removed and contralateral herniorrhaphy and orchiectomy were recommended. The animal showed complete healing of the surgical wound, but did not return for treatment of the contralateral inguinal hernia. Discussion: Inguinal hernia is considered rare in male dogs, especially in non-neutered animals, and few cases have been described, most of which are over the age of four years. In the present report, the dog is male, not neutered and is eight years old, in line with the findings of the highest occurrence in this species. Inguinal hernia can be hereditary, congenital or acquired from trauma or hormonal changes, and its etiology is poorly understood. The dog in this report acquired this condition in adulthood, and it was not possible to define the cause of the hernia, however it is believed that there is a possibility of muscle weakness associated with the patient's weight. Inguinal hernia in non-neutered dogs usually progresses to inguino-scrotal hernia, and cases in the Brazilian queue breed have been described. In this work, the herniated content was irreducible contrary to what is generally reported. In inguinal hernia, the most observed content is the intestinal loops, but the bladder and colon have already been seen. In the animal in this report, the spleen appeared as herniated content. The diagnosis can be made by palpation when the hernia is reducible, but it does not allow the definition of the hernia content. In cases of incarcerated hernias, it is necessary to perform an ultrasound which also allows the definition of the hernia content. The recommended treatment is surgical by herniorrhaphy, as was done in this patient. During surgery, muscle atrophy was observed in the inguinal region, but the tutor did not authorize the placement of polypropylene mesh for financial reasons. The alternative used and authorized by the tutor was the use of a biological membrane that achieved a satisfactory result, with few complications in the postoperative period.